The Effects of Parenting in Family of Jama'ah Tabligh toward Children's Social Quotinent - Zalnur, Muhammad; Japeri, Japeri; Thuwaiba, Thuwaiba (Islamic Studies and Development Center in collaboration with Department of Islamic Education Universitas Negeri Padang, 2024)
Social intelligence is a skill that Allah SWT has given to humans to enable them to adapt to their surrounding environment. Only some humans can have it if it is not accompanied by maximum training from an early age, coupled with the influence of technological developments which can make humans busy with their world. This research explores the effect of parental education in the Tablighi Jama'ah family on children's social intelligence. This research uses qualitative methods with an ethnographic approach, research data was taken through direct interviews with ten informants (heads of Tablighi Jama'ah families), to strengthen the interview data the author conducted observations for two years by being directly involved in Tablighi Jama'ah activities such as Ijtima’, Bayan Markas, Ta’lim Halaqah, Khuruj, Jaulah and it is not uncommon for the author to visit directly at the homes of all the informants. All interview and observation data were then analyzed using technical methods Analysis Interactive Model Milles & Hubberman with the help of NVIVO 12.0 Software. Overall, the research findings found five main themes of the impact of parental education based on the Tablighi Jama'ah preaching on children's social intelligence. The five themes are; i) likes to encourage friends to do good things, ii) worries about seeing friends skipping prayers, iii) likes to advise friends who are inconsistent in worship, iv) empathizes with friends who are affected by disaster, v) is active in doing good deeds. The five findings in this research have proven that parental education based on Tablighi Jama'ah preaching has a positive impact on children's social intelligence in the family and society.